Fatal acute hypernatremia resulting from a massive intake of seasoning soy sauce. Issue 1 (20th August 2020) - Sakamoto, Ayaka; Hoshino, Tetsuya; Boku, Keishun; Hiraya, Daigo; Inoue, Yoshiaki
Abstract : Background: Hypernatremia due to salt poisoning is clinically rare and standard care procedures have not been established. We report a case of salt poisoning due to massive intake of seasoning soy sauce. Case Presentation: A 40‐year‐old woman presented to the emergency department with seizures and remarkable hypernatremia with a serum sodium concentration of 183 mEq/L. The initial brain computed tomography scan showed brain shrinkage, which could occur during the acute phase of hypernatremia. We reduced her serum sodium level rapidly, rather than at the recommended slow rate. On day 3, the patient's brain computed tomography scan showed widespread low‐density areas and edema. The patient died 8 days after admission. Conclusion: After reviewing instances of resuscitation following salt intoxication, aggressive rapid correction of serum sodium concentration should only be considered in acute phases of hypernatremia within a few hours from ingestion, and 2–3 h could be one of the criteria. Abstract : Hypernatremia due to salt poisoning is clinically rare and standard care procedures have not been established. We report a case of salt poisoning due to massive intake of seasoning soy sauce. Aggressive rapid correction of serum sodium concentration should only be considered in acute phases of hypernatremia within 2–3 h of salt ingestion, before the brain cells adapt to high osmolarity.